Biomedical image understanding : methods and applications - Lim, Joo Hwee, 1964-; Ong, Sim Heng, 1955-; Xiong, Wei, 1966- (John Wiley & Sons Inc., 2014)
Biomedical Image Understanding focuses on image understanding and semantic interpretation, with clear introductions to related concepts, in-depth theoretical analysis, and detailed descriptions of important biomedical applications. It covers image processing, image filtering, enhancement, de-noising, restoration, and reconstruction; image segmentation and feature extraction; registration; clustering, pattern classification, and data fusion.